Synthesized flavanoid-derived ligand reduced dengue virus type-2 replication in vitro - Muhamad, M.; Lee, Y.K.; Rahman, N.A.; Yusof, R. (Elsevier, 2017)
Objective To investigate the antiviral property of a lead ligand, YK51 that was synthesized based on the flavanoid of a natural product toward dengue virus type-2 (DENV2) replication. Methods cRNA was isolated from HepG2 cells inoculated with 1 000 median tissue culture infective dose of DENV2 and treated with different doses of the ligand followed by RT-PCR to quantify the virus gene copies. Confocal microscopy of actin and tubulin redistribution was also performed. Results The quantitative RT-PCR result showed reduction of the DENV2 gene copies as the ligand concentration was increased. The confocal microscopy result showed increase in the tubulin intensity (79.6%) of infected BHK21 cells treated with the ligand, compared with the non-treated cells (54.8%). The 1.5-fold increase in the intensity of tubulin suggested that the ligand inhibitory effect stabilized the cellular microtubule structure. Conclusions The synthesized ligand YK51 reduced DENV2 viral load by inhibiting virus replication thus is highly potential to be developed as antiviral agent.